Annual Plan 1981-82 - Planning Commission (Planning Commission, 1981)
The Annual Plan for 1981-82, which in the second year of the Sixth Five Year Plan 1980-85, has been formulated against the background of the economic situation obtaining in 1980-81 and within the framework of the objectives and priorities envisaged in the new Five Year Plan. It aims at consolidating the gains of the recovery achieved in 1980-81, removing the constraints operating in the economy and creating necessary conditions for orderly development and achievement of the socio-economic objectives outlined in the Sixth Plan. The main thrust is towards promoting optimal growth along with expansion of opportunities for productive employment, particularly in rural areas, and improvement of the living conditions of the poorer and weaker sections of the community.
Government of India Planning Commission
Government of India Planning Commission